Birth Control Knowledge among Pharmacy Undergraduate Students in Vietnam: A Case Study and Situation Analysis - Quang Vo, Dr.Trung (Asian Journal of Pharmaceutics (AJP), 2018)
Aims: The main goal of this study is to define the factors that contribute to the knowledge, awareness, perceptions, and practice of birth control among pharmacy students at Lac Hong University (LHU) in Dong Nai Province. Subjects and Methods: A prospective cohort study was conducted among pharmacy students over 4 months from September to December 2017. Results: All respondents (n = 403) had heard of birth control methods. Nearly 90% of participants indicated that the male condom can protect against sexually transmitted diseases. Condoms are also the most common method of birth control. The mean knowledge and awareness scores of students were 4.52 ± 1.420 and 20.67 ± 4.06, respectively. The highest birth control knowledge score was 5.64 ± 0.996. Fifth-year students were the most knowledgeable about contraceptive use and had the highest mean knowledge score (4.82 ± 1.307). A significant association was found between marital status (P < 0.001), religion (P < 0.05), and mean knowledge of the respondents. Conclusions: Overall, the findings reflect that the majority of students at LHU had a poor understanding and awareness of contraception methods. Health education and awareness programs should be initiated for students to provide them with correct knowledge about contraception. The knowledge of these future health-care professionals will play an important role in improving public health.